Challenges in the sociocultural milieu of South Asia: a systematic review of community health workers - Umair Majid; Mahrukh Zahid; Kate Harold; Shahzadi Zain; Tushar Sood (James Cook University, 2021)
Introduction: Community health workers (CHWs) connect patients in rural and remote communities to health service organizations. This diverse group of healthcare workers has helped improve healthcare access and outcomes and enhance the quality of life for people in hard-to-reach communities. However, CHWs face numerous challenges rooted in the sociocultural milieu of the region and country in which they reside. Methods: This systematic review and qualitative meta-synthesis of 38 studies examines the sociocultural challenges that CHWs experience; it focuses on the unique history, geography, and sociocultural milieu of South Asia. Results: This study found the following challenges that CHWs regularly face when working in communities: religious and cultural norms and practices, gender and biological sex, caste, and generation. All challenges in some way relate to one another and stem from the unique sociocultural milieu of South Asia, and the various subcultures that exist in this diverse region. Conclusion: This article presents important guidance for program planning and CHW deployment that reflects the sociocultural realities of practice. The findings of this investigation may serve as an essential resource for program planners and decision-makers in improving the effectiveness and reach of CHW programs.